Critical factors of service quality in a graduate school of Malaysia - Ahmad, Khaliq; Abd. Manaf, Noor Hazilah; Ahmad, Selim (Emerald, 2013)
Abstract Purpose – This paper aims to evaluate the service quality of a higher educational institute in Malaysia based on the seven dimensions, namely administrative service, tangibles, academic programmes, academic staff, delivery of teaching, assurance, and empathy of academic staff.